2018
DOI: 10.3747/co.25.3892
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Routine Follow-Up Care After Curative Treatment for Head-and-Neck Cancer: A Population-Based Study in Ontario

Abstract: BackgroundThe actual practices of routine follow-up after curative treatment for head-and-neck cancer are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Decision making in follow‐up care would be reduced in complexity if there were higher level evidence available on the subject, rather than consensus‐based guidelines developed outside of Canada. The results of this study, a description of HNC patients’ well‐being and needs in routine follow‐up as well as our research team's recent efforts to outline current practices in the real‐world (Brennan, Hall, Owen, Griffiths, & Peng, ) aid in laying the ground work necessary to plan a future Canadian trial.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Decision making in follow‐up care would be reduced in complexity if there were higher level evidence available on the subject, rather than consensus‐based guidelines developed outside of Canada. The results of this study, a description of HNC patients’ well‐being and needs in routine follow‐up as well as our research team's recent efforts to outline current practices in the real‐world (Brennan, Hall, Owen, Griffiths, & Peng, ) aid in laying the ground work necessary to plan a future Canadian trial.…”
Section: Discussionmentioning
confidence: 98%
“…well-being and needs in routine follow-up as well as our research team's recent efforts to outline current practices in the real-world (Brennan, Hall, Owen, Griffiths, & Peng, 2018) aid in laying the ground work necessary to plan a future Canadian trial.…”
Section: Con Clus I On and Future Workmentioning
confidence: 99%
“…"When there is no evidence, practice will vary" 20 . In a previously reported study based on 3675 patients, we assessed the variation in hnc follow-up in Ontario 21 . We found marked variation in all aspects of follow-up (including frequency of appointments), without substantial relationship to guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…A study analyzing surveillance testing in Canada found similar variations, with male sex, surgery as treatment, and lower income quintiles associated with fewer than recommended follow-up visits. 26 Although the socioeconomic status, income, and education level were extrapolated from place of residence in our study and were only moderately reflective of an individual's socioeconomic status, it is worth emphasizing the importance of understanding survivorship needs across cultures and socioeconomic status as we strive toward equitable, high-quality cancer survivorship care. 27 Recent guidelines have also described the role of PCPs in HNC survivorship; the comprehensiveness of their role coupled with a lack of expertise in these domains may underscore practical challenges that have not been fully explored.…”
Section: Discussionmentioning
confidence: 99%